Improving the Quality of Personnel in the Field of Technology Through the Effective Organization of Independent Education (Journal of Pedagogical Inventions and Practices, 2023)
In this article, the problems of organizing independent education, one of the main problems of higher education institutions transitioning to the credit module system, and recommendations for solving them have been developed. The article describes the problems of the effective organization of independent education in higher educational institutions in technology. In addition, the analysis of external and internal factors in the organization of effective independent education and effective use of Internet resources by students is provided.